Rectus femoris muscle injuries in football: a clinically relevant review of mechanisms of injury, risk factors and preventive strategies - Mendiguchia, J.; Alentorn-Geli, E.; Idoate, F.; Myer, G. D. (British Journal of Sports Medicine, 2013)
Quadriceps muscle strains frequently occur in sports that require repetitive kicking and sprinting, and are common in football in its different forms around the world. This paper is a review of aetiology, mechanism of injury and the natural history of rectus femoris injury. Investigating the mechanism and risk factors for rectus femoris muscle injury aims to allow the development of a framework for future initiatives to prevent quadriceps injury in football players.